2016
DOI: 10.1021/acs.orglett.6b03156
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Continuous-Flow Cyclopropanation

Abstract: A set of six solid-supported diarylprolinol catalysts (varying on the anchoring strategy and the type of polymeric support) has been prepared and applied to the enantioselective cyclopropanation reaction. The selected candidate allows implementation of a long flow experiment (48 h) and generates a library of 12 cyclopropanes by sequential flow experiments. The mildness and utility of the method have enabled a telescoped process in which the outstream is directly used in a Wittig flow reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…More efficient and already veried supports such as organic polymers [29][30][31][32][33][34][35] or nanoparticles 36,37 have, however, not been considered in this study. The obvious reason is that we aimed for simultaneous use of the new materials as continuous ow organocatalysts and stationary phases for HPLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More efficient and already veried supports such as organic polymers [29][30][31][32][33][34][35] or nanoparticles 36,37 have, however, not been considered in this study. The obvious reason is that we aimed for simultaneous use of the new materials as continuous ow organocatalysts and stationary phases for HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…The current approach to address this problem involves immobilization of the catalyst to a solid support. 28 Several types of solid matrices, such as polystyrene, [29][30][31][32][33][34][35] metal nanoparticles, 36,37 metalorganic frameworks, 38 ion-modied resins for non-covalent binding, [39][40][41] or mesoporous silica [42][43][44][45] have been introduced as solid supports for various types of organocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Enantioselective cyclization reactions : One study on enantioselective cyclopropanation was reported by Pericàs and co‐workers . Six solid‐supported diarylprolinol catalysts were prepared to analyze which immobilization method gave the best enantioselectivity in the cyclopropanation of enals 79 with dimethyl bromomalonate 80 (Scheme ).…”
Section: Heterogeneous Enantioselective Catalysis In Flowmentioning
confidence: 99%
“…In order to dig into this issue, we selected the diarylprolinol‐catalyzed cyclopropanation of α,β‐unsaturated aldehydes as a touchstone. Thus, a library of supported catalysts ( 8 – 10 ) was prepared with two points of diversity: the type of resin and the immobilization strategy . For the resin, we chose a microporous polystyrene resin (low cross‐linking) or a macroporous monolith; the three immobilization strategies to be compared were (a) a hydroxyproline with a benzylic linker ( 8 ), (b) a triazole‐based 9 and (c) a co‐polymerization approach analogous to the one followed for 10 (Figure ).…”
Section: Immobilized Organocatalysts For Work In Flowmentioning
confidence: 99%
“…Thus, a library of supported catalysts (8-10) was prepared with two points of diversity: the type of resin and the immobilization strategy. [49] For the resin, we chose a microporous polystyrene resin (low cross-linking) or a macroporous monolith; the three immobilization strategies to be compared were (a) a hydroxyproline with a benzylic linker (8), (b) a triazole-based 9 and (c) a co-polymerization approach analogous to the one followed for 10 [47] (Figure 9). Catalysts 8-10 were thus tested in batch in the abovementioned cyclopropanation reaction; the results show that the parameters under study significantly affect the performance of the resin.…”
Section: Diarylprolinol Derivativesmentioning
confidence: 99%